Fighting Depression: Action Video Game Play May Reduce Rumination and Increase Subjective and Objective Cognition in Depressed Patients - Kühn, Simone; Berna, Fabrice; Lüdtke, Thies; Gallinat, Jürgen; Moritz, Steffen (Frontiers in Psychology, 2018)
Cognitive deficits are common in depression, are known to play a role in functional recovery, and may persist following the resolution of affective symptoms. However, therapeutic strategies that successfully target cognitive impairments are lacking. Recent work has demonstrated that playing action video games leads to improvements in cognition, in particular executive function, in healthy individuals. We therefore set out to test whether playing video games can reduce symptoms associated with depression. We focussed on depressive symptoms and on rumination, since rumination is a good predictor of depression and may contribute to triggering depression. We recruited 68 clinically depressed individuals (mean age: 46 years, 47 females) that were randomized into the training group playing a fast paced action video game for six weeks or a waitlist control group. Before and after training participants completed online questionnaires and a neuropsychological test battery. Only participants who actually had played the game were included in the analysis. The final sample consisted of n = 21 training group and n = 29 waitlist control group. The training group showed significantly higher subjective cognitive ability, as well as lower self-reported rumination at posttest in contrast to the control group (although these findings do not survive Bonferroni correction). On a subsample with cognitive performance data (n = 19) we detected an improvement in executive function (Trail Making Task A and B) in the training compared with the control group. The results show that the fast paced action video game employed in the present study improved Trail Making performance and may reduce rumination and enhance subjective cognitive ability. Future research may focus on the investigation of the precise cognitive profile of effects.